2021
DOI: 10.1182/bloodadvances.2020002417
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic and anti-inflammatory effects of bortezomib on systemic chronic active EBV infection

Abstract: Systemic chronic active Epstein-Barr virus (EBV; sCAEBV) infection, T- and natural killer (NK)-cell type (sCAEBV), is a fatal disorder accompanied by persisting inflammation harboring clonal proliferation of EBV-infected T or NK cells. Today’s chemotherapy is insufficient to resolve disease activity and to rid infected cells of sCAEBV. The currently established treatment strategy for eradicating infected cells is allogeneic hematopoietic stem cell transplantation. In this study, we focused on the effects of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…CMV and EBV are the most closely related clinical viruses with a clear therapeutic association (Einsele et al, 2020;Yoshimori et al, 2021). There seems to be a bidirectional relationship between the two viruses, and a high incidence/low clearance rate of CMV infection and a high incidence and delayed immune reconstitution of EBV-PTLD are key to all of these findings (Green et al, 2013;Chiereghin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CMV and EBV are the most closely related clinical viruses with a clear therapeutic association (Einsele et al, 2020;Yoshimori et al, 2021). There seems to be a bidirectional relationship between the two viruses, and a high incidence/low clearance rate of CMV infection and a high incidence and delayed immune reconstitution of EBV-PTLD are key to all of these findings (Green et al, 2013;Chiereghin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous report, ruxolitinib, a JAK1/2 inhibitor suppressed STAT3 activation and IFN-γ production of EBV-positive NK cells in patients' cells [22]. Recently, we also observed that a proteasome inhibitor bortezomib suppressed IFN-γ production not only in EBV-positive T-or NK-cells but also in xenograft model of CAEBV [32]. Additionally, emapalumab, a neutralizing anti-IFN-γ monoclonal antibody has been reported for its efficacy to treat primary HLH [33].…”
Section: Discussionmentioning
confidence: 69%
“…Our results showed that simvastatin induced growth inhibition and apoptosis in sCAEBV cells, and, moreover, reduced the viral load of EBV-DNA in PB of the xenograft models. We recently reported the effects bortezomib, a proteasome inhibitor, on sCAEBV xenograft models 13) . The mice with significantly decreased EBV-DNA load in PB clearly showed reduced infiltration of EBV-positive cells in the liver.…”
Section: Discussionmentioning
confidence: 99%